The Concept of Islamic Education for Nonmarital Children: A Comparative Analysis of the Thoughts of Muhammad Syahrur and Abdullah Nasih Ulwan - Ratna Pangastuti,; Kunawi Basyir,; Abdul Azis,; Uswatun Chasanah ,; Taseman,; Mohammad Wildan Alfani, (TADRIS: Jurnal Pendidikan Islam, 2024)
This article examines the comparative analysis of Abdullah Nasih Ulwan`s thoughts with Muhammad Syahrur regarding the parenting of non-marital children.Departing from the current social phenomenon of society which indicates the number of children born from non-marital realtions, where as individuals who are born naturally, children ideally have the right to be able to live properly like other children resulting from marital relations in giving their obligations and right to children as natural and holy individuals in the Islamic view as in hadith narrated by the Prophet.This paper uses a descriptive qualitative approach with a type of literature review. Analyzing Abdullah Nasih Ulwan’s thought about the role of parents in giving obligations and rights to non-marital children, as well as how Muhammad Syahrur’s thoughts with his theory of milk al-yamin views the obligations and rights of parents toward children as parents’ obligations to chidren through the marital route,as explained by Ulwan about parenting. This was because Syahrur aligned milk al-yamin with marriages of th types mut`ah,misyar, and etc.